THE TEACHING OF EFL LISTENING IN THE INDONESIAN CONTEXT: THE STATE OF THE ART - Bambang Yudi Cahyono (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: The status of English as a foreign language (EFL) in Indonesia necessitates the use of English native speakersÃ¢â¬â¢ utterances as models of pronunciation and as standard of understanding messages in various contexts, be they academic or social. As recently English has developed as an international language that can be used as a means of communication between people from non-English speaking countries, the role of listening activities in the teaching of English cannot be neglected. This article highlights the importance of listening and reviews some of the issues in the research and teaching of EFL listening. It firstly presents a paradigm of the listening process, followed by a theoretical framework for teaching listening, especially in the broader context of English language teaching. It then discusses the teaching of and research on EFL listening in Indonesia. Finally, this article outlines some recommendations for more effective teaching of listening in EFL classrooms.